Self Control, Motivation and Cyberloafing on the Performance of High School and Vocational School Employees in Tarakan during the COVID 19 Pandemic - Widyastuti Cahyaningrum; Annisa Eka Yulianti (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the effect of self control, motivation and cyberloafing behavior on the performance of school employees (SMA and SMK) in Tarakan City. This research uses a quantitative approach with a survey method. The population and sample in this study were employees of State High Schools and Vocational High Schools in Tarakan City. The sample in this study was 110 respondents with purposive sampling and was calculated using the formula according to Hair et al (2010). Furthermore, hypothesis testing was carried out using multiple linear regression models with the t test using the SPSS program. The results showed that self-control has a positive effect on employee performance, motivation has a positive effect on employee performance and cyberloafing has no effect on school employee performance.